ANALISIS NILAI PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yuwaffa Muhammad Sulthan; Siwi Nugraheni (Veteran Economics, Management, & Accounting Review, 2023)
This study aims to 25nalyse the effect of profitability, investment decisions, leverage and inflation on firm value. The study used a quantitative approach.sector companies, real estate while the sample used is 44 companies for the 2017-2020 period which was taken by purposive sampling method.The analytical method used is panel data regression analysis technique using Eviews 12software. The results show that profitability and investment decisions have no effect on firm value while leverage and inflation have a positive effect on firm value. Keywords: profitability; investment decisions; leverage; inflation